Study Of Sae Dating Program In Improving Marriage Readiness Based On Law And Religious Teachings - Yuliastuti, Eko; Hakam Sholahuddin, Abdul; Trijaya Febrianti, Afeleni (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The “Kencan Sae” program is an innovative initiative by the Blitar City Government to assist unmarried individuals through premarital socialization and matchmaking. This study uses a descriptive qualitative method with data collection through in-depth interviews and field observations. The results of the study show that the program has been routinely implemented since April 2025 in various public facilities with material on mental and social readiness and the legal and religious values of marriage. The program is in line with the Marriage Law (No. 1/1974 jo. No. 16/2019) and Islamic teachings that emphasize physical, mental, and economic readiness before marriage. Participants generally appreciated the effectiveness of this program, although challenges such as participant awareness and resource limitations emerged as obstacles. Based on the findings, it was concluded that Kencan Sae can improve the legal and religious readiness of prospective brides and grooms and has the potential to reduce the rate of early marriage. Recommendations were made to expand outreach and strengthen cross-sector support to maximize the program's impact.